History of the Origin of Dutar. General Rules of Dutar Performance and Improving Performance Skills - Muqaddas, Quvondikova (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is devoted to the history of the origin of the dutar, the general rules of dutar performance and the development of performance skills.In the article you can find answers to questions such as the family of dutars, their creation, why they were reproduced, dutar timbres and so on. In addition, according to my own practice, I gave information about the importance of technical improvement in the performance process, gamma, etudes and exercises in the performance of the work.